2003
DOI: 10.1038/sj.gt.3302050
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of linear and branched polyethylenimine (PEI) with DCChol/DOPE liposomes for gene delivery to epithelial cells in vitro and in vivo

Abstract: Polyethylenimine (PEI), a polycation with high ionic charge density, has recently been used as a gene therapy delivery agent. We have defined the optimal conditions for PEI-based transfection of airway epithelial cells in vitro and in vivo and used these conditions to restore Cl À channel activity in a CF mouse model. Three forms of PEI, a linear 22 kDa (ExGen 500) form and branched 25 or 50 kDa forms were evaluated. All forms of PEI significantly increased luciferase reporter gene expression compared to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
148
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(150 citation statements)
references
References 31 publications
1
148
0
1
Order By: Relevance
“…Among them, L-PEI was chosen for its ability to lead to robust transgene expression in vivo following various administration routes. 2,3,[23][24][25][27][28][29] Moreover, it has been previously demonstrated that linear PEI is more efficient than the branched polymer in vitro and in vivo, 4,30,31 and Figure 4 b-Galactosidase activity in tumor nodes developed on the peritoneal wall of mice transfected with 100 or 250 mg DNA, evaluated 24 h after injection as described in Materials and methods.…”
Section: Discussionmentioning
confidence: 98%
“…Among them, L-PEI was chosen for its ability to lead to robust transgene expression in vivo following various administration routes. 2,3,[23][24][25][27][28][29] Moreover, it has been previously demonstrated that linear PEI is more efficient than the branched polymer in vitro and in vivo, 4,30,31 and Figure 4 b-Galactosidase activity in tumor nodes developed on the peritoneal wall of mice transfected with 100 or 250 mg DNA, evaluated 24 h after injection as described in Materials and methods.…”
Section: Discussionmentioning
confidence: 98%
“…[20] A number of studies have shown that, in selected cell lines, branched PEI generates stronger transgene expression that linear PEI. [18,31] In contrast, when PEI is injected intravenously or via the lungs, linear PEI, generates stronger transgene expression than branched PEI. [31,34] In vitro studies show that increasing the N:P ratio of the PEI-pDNA nanoparticles increases luciferase activity and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[13,30,31] Several studies have shown that linear PEI generates stronger transgene expression in vivo when injected intravenously or administered via the lung in comparison to branched PEI at equivalent molecular weights. [24,[31][32][33][34][35] In contrast, other studies have shown that branched PEI generates stronger transgene expression than linear PEI in vitro in selected cell lines. [18] Some studies have shown that linear PEI is more efficient than branched PEI in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Cationic lipids are typically composed of a positively charged head group, a flexible linker group (e.g., an ester or ether), and two or more hydrophobic tail groups. [5] For improving transfection efficiency, cationic lipids are often mixed with helper lipids such as cholesterol or DOPE (1, 2-dioleyl-sn-glycerol-3-phosphoethanolamine) potentially promoting conversion of the lamellar lipoplex phase into a hexagonal structure.…”
Section: Lipid-based Non-viral Vectorsmentioning
confidence: 99%